PENGARUH FAKTOR DEMOGRAFI DAN PRODUCT KNOWLEDGE DALAM MEMPENGARUHI EMOSI PERILAKU KONSUMEN SKINCARE PREMIUM ESTEE LAUDER DI SURABAYA - Ramadhan, Sani; Faidah, Mutimmatul; Puspitorini, Arita; Kecvara Pritasari, Octaverina (Jurnal Tata Rias, 2025)
The use of skincare among Indonesian people continues to increase and develop with the times. Estee Lauder is one of the foreign brands that is quite popular in Indonesia. This research aims to examine the influence of demographic factors and product knowledge on the emotion and social status of Estee Lauder premium skincare consumers in Surabaya. The research used is an analytical observational type with a cross sectional approach. The population in this research is Estee Lauder consumers in Surabaya with a sample of people who use Estee Lauder skincare. The research instrument is a questionnaire instrument with data analysis using percentages then analyzing the relationship with multiple linear regression and hypothesis testing with the F test and t test. The research results showed that demographic factors consisting of age, gender, education, employment and income had a positive effect on emotional and social status and product knowledge factors had a positive effect on emotion and social status.Keyword : Skincare, Demographics and Product Knowledge, Estee Lauder.